Association of Chinese visceral adiposity index with asymptomatic hyperuricemia incidence in type 2 diabetes: a cross-sectional study - Qing Wang; Tian Liu; Changxin Jia; Ping Wang; Yangang Wang; Qing He (PeerJ)
Background Previous research has shown a correlation between high visceral fat levels and hyperuricemia incidence. The Chinese Visceral Adiposity Index (CVAI) assessed visceral fat status in the Chinese population. Our study investigates the correlation between CVAI and asymptomatic hyperuricemia in type 2 diabetes patients. Methods This cross-sectional study analyzed 1,588 hospitalized type 2 diabetes patients to investigate the association between CVAI and hyperuricemia. CVAI was included in the logistic regression analysis as both a continuous and categorical variable, and restricted cubic splines were used to assess the dose-response relationship. Additionally, subgroup analyses were performed to investigate potential interactions among variables. The predictive capability of CVAI was assessed using the receiver operating characteristic (ROC) curve based on the basic model. Results The CVAI quartile group analysis revealed a higher prevalence of hyperuricemia with increasing CVAI levels. CVAI is significantly associated with hyperuricemia, as identified through multifactorial logistic regression analysis. After adjusting for all covariates, the odds ratios for CVAI in the second, third, and fourth quartiles were significantly higher than in the lowest quartile, with values of 2.688 (95% CI [1.301–5.554], p = 0.008), 2.752 (95% CI [1.320–5.739], p = 0.007), and 4.990 (95% CI [2.392–10.409], p < 0.001), respectively. No significant interactions were observed in the subgroup analysis. Incorporating CVAI into the basic model increased the ROC curve’s area under the curve to 0.714. Conclusion This study found a positive correlation between CVAI and hyperuricemia incidence in type 2 diabetes patients. Consequently, CVAI may reliably indicate hyperuricemia in this patient population.